Phraseological Units in the French Language: Cognitive Comprehension and Pragmatic Implementation in the Communication Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Phraseological units in the French language serve as vital cognitive and pragmatic instruments, encapsulating cultural values and facilitating efficient communication. These fixed expressions, characterized by metaphorical richness and structural stability, reflect collective cognition and social norms. This paper examines the cognitive foundations of French phraseological units, analyzing their semantic and structural features, as well as their pragmatic functions in discourse. Additionally, it explores their cultural embeddedness, variations, and implications for language pedagogy and translation. By bridging linguistic structures with human experience, French phraseological units enhance communicative competence and cultural literacy, underscoring their significance in both theoretical and applied linguistics.